Extension of the Universal Force Field to Metal–Organic Frameworks - Addicoat, Matthew A; Vankova, Nina; Akter, Ismot Farjana; Heine, Thomas (Journal of chemical theory and computation, 2014)
The Universal Force Field (UFF) (Rappé et al., J. Am. Chem. Soc. 1992) provides a general approach to molecular mechanics for molecules and materials composed of elements throughout the periodic table. Though the method is tunable by the specification of bond orders and the introduction of effective charges, the presently available list of atom types is insufficient to treat various systems containing transition metals, including metal–organic frameworks (MOFs). As MOFs are composite materials built of a combination of individually stable building blocks, a plethora of MOF structures are possible, and the prediction of their structure with a low-cost method is important. We have extended the UFF parameter set to include transition metal elements Zn, Cu, Ni, Co, Fe, Mn, Cr, V, Ti, Sc, and Al, as they occur in MOFs, and have proposed additional O parameters that provide reliable structures of the metal oxide clusters of the connectors. We have benchmarked the performance of the MOF extension to UFF (UFF4MOF) with respect to experimentally available data and to DFT calculations. The parameters are available in various well-spread programs, including GULP, deMonNano, and ADF, and all information is provided to include them in other molecular mechanics codes.